Pemikiran Abu Bakar Bin Al-Markhum Muhammad Syato’ tentang Karakter dalam Kitab Kifayatul Atqiya’ wa Minhaju Asfiya’ - M. Syarif (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2020)
Kifayat al-Atqiya is a guide book written by Sufi Ulama Abu Bakar Bin Al-Markhum Muhammad Syato ', inviting every muslim to be a totally good creature, in the eyes of God and humans, taught through the touch of morality-Sufism. The focus of this research is about the values ​​of character education contained in the book Kifayat al-Atqiya by Abu Bakar Bin Al-Markhum Muhammad Syato'. It is against the background of the declining position of moral education in the community. Various problems related to morals began to arise to cause moral degradation. Therefore, it is necessary to study about moral education which is expected to provide enlightenment. Nowadays character education really needs to be developed in the world of education because of the importance of character keys in the development of a nation and country. Before the term character was echoed in education in Indonesia long ago it was instilled and taught by Rasulallah through Allah's revelation in the form of the Al-quran which was then continued by the alim ulama one of which is the thought of Abu Bakr Bin Al-Markhum Muhammad Syato'.